Anaerobic co-digestion of multiple agricultural residues to enhance biogas production in southern Italy. (August 2018) - Valenti, Francesca; Zhong, Yuan; Sun, Mingxuan; Porto, Simona M.C.; Toscano, Attilio; Dale, Bruce E.; Sibilla, Fabrizio; Liao, Wei
Highlights: Citrus pulp and olive pomace are beneficial for biogas production. Anaerobic digestion is a suitable technology to manage agricultural wastes in Sicily. The co-digestion with high citrus pulp content takes longer to be stabilized. Abstract: To valorize agricultural wastes and byproducts in southern Italy, anaerobic co-digestion of six feedstocks (citrus pulp, olive pomace, cattle manure, poultry litter, whey, and corn silage) was studied to produce biogas for renewable energy generation. Both batch and semi-continuous co-digestion approaches were adopted to carry out the investigation. The feedstocks were mixed at different percentages according to their availabilities in southern Italy. The batch anaerobic co-digestion demonstrated that six studied feedstock mixtures generated an average of 239 mL CH4 /g VS loading without significant difference between each other, which concluded that the feedstock mixtures can be used for biogas production. Considering the feedstock availability of citrus pulp and olive pomace in Sicily, three feedstock mixtures with the highest volatile solids concentration of citrus pulp (42% citrus pulp, 17% corn silage, 4% cattle manure, 8% poultry litter, and 18% whey; 34% citrus pulp, 8% olive pomace, 17% corn silage, 4% cattle manure, 8% poultry litter, and 18% whey; and 25% citrus pulp, 16% olive pomace, 17% corn silage, 4% cattle manure, 8% poultry litter, and 18% whey, respectively) were selected to run the semi-continuous anaerobic digestion. Under the stabilized culture condition, the feed mixture with 42% citrus pulp, 17% corn silage, 4% cattle manure, 8% poultry litter, and 18% whey presented the best biogas production (231 L methane/kg VS loading/day). The corresponding mass and energy balance concluded that all three tested feedstock mixtures have positive net energy outputs (1.5, 0.9, and 1.2 kWh-e/kg dry feedstock mixture, respectively).